Answer:
See details below
Explanation:
To verify that y=f(x) is a solution of the differential equation in some interval (where f is defined), we take derivatives respect to x using the usual rules (sum, product, chain rule, exponential,...)
a)
![y=ce^(2x)\rightarrow y'=(2x)'ce^(2x)=2ce^(2x)=2y](https://img.qammunity.org/2021/formulas/mathematics/college/uz8tjjvwmipv0650mss9dd3pqt4k9xvb3i.png)
b)
![y=(x^2)/3+c/x \rightarrow xy'+y=x( 2x/3 -c/x^(2) )+(x^2)/3+c/x =3x^2/3-c/x+c/x=x^2](https://img.qammunity.org/2021/formulas/mathematics/college/2ityrosof3hpislyfltbfh0yyb9mlnsc8c.png)
c) The solution of the differential equation is slightly different (the function given is a solution only if c=0)
![y=1/2 + ce^((-x^2)) \rightarrow y'+2xy=((-x^2))'ce^((-x^2))+2x(1/2 + ce^((-x^2)) )=-2cxe^((-x^2))+x+2cxe^((-x^2))=x](https://img.qammunity.org/2021/formulas/mathematics/college/970lizpdt2uft9ds7zxnx09lsfsjcf8lxs.png)
d)
![y=1+c e^((-x^2)/2)) \rightarrow 2y'+x(y^2-1)=2(-xce^(x^2/2))+x(1+2ce^(x^2/2)+c^2e^(-x^2)-1)=-2xce^(x^2/2)+2xce^(x^2/2)+c^2e^(-x^2)=c^2e^(-x^2)=0](https://img.qammunity.org/2021/formulas/mathematics/college/7y6mbc5fes2y4ld8nwa3i0cmsriy143def.png)
only if c=0, this also happens for the other function.